THE EFFECT OF USING RING THEORY MOBILE APPLICATION ON STUDENT INVOLVEMENT AND REASONING ABILITY - Suryanti, Sri; Sutaji, Deni (Journal on Mathematics Education)
This study aims to determine the influence of the use of ring theory mobile application on student involvement in learning and the students reasoning ability. The subject of research is sixth-semester students who take the subject of Ring Theory that is 30 people. The research instrument used is observation sheet, student involvement questionnaire, and test questions to know students reasoning ability. The research method used is descriptive quantitative to know the involvement of students, while to know the effect on students reasoning ability used independent sample t-test with SPSS 15.0. The results showed that the use of ring theory mobile application caused a very positive engagement, from the overall indicator of student involvement in learning, gets an average scoreÂ  4.74 (score range 1-5). Also, there was a significant influence of the use of ring theory mobile application on students reasoning ability, which is 0.721